Assess the Incidence of Peripheral Neuropathy in Recently Diagnosed Cases of Type II Diabetes Mellitus - Nabi, Nimra; Yousafzai, Hira Bibi; Afzal, Muhammad; Babar, Masood Uz Zaman; Farooq, Waqas; Khan, Khaiber (Journal of Neonatal Surgery, 2025)
Background: Type II Diabetes Mellitus comes with a significant morbidity due to the common complication of peripheral neuropathy. It is vital to identify early in order to control and avoid more complications. Objective: The purpose of this study was to assess the incidence of peripheral neuropathy in recently diagnosed cases of type ii diabetes mellitus Material and Methods: This is a cross sectional study carried out at Sharif Medical and Dental College Lahore November 2022 to May 2024. 350 newly diagnosed Type II Diabetes Mellitus patients were recruited into the study. The Michigan Neuropathy Screening Instrument (MNSI) was used to assess peripheral neuropathy status. Age, BMI, symptom duration and hypertension status were collected as demographic and clinical data. Descriptive statistics and Chi square tests for categorical comparisons using p ≤ 0.05 were used on data analysis. Results: The mean age of patients was 56.01 years (SD = 11.231), with a mean symptom duration of 12.53 weeks (SD = 6.921) and a mean BMI of 27.88 (SD = 3.605). The prevalence of peripheral neuropathy was 31.4% (n=110). A significant association was found between age and neuropathy, with prevalence increasing from 17.9% in the 35-49 age group to 41.0% in patients aged 65-74 years (p=0.001). Obesity was also significantly associated with neuropathy, with 56.6% of obese patients affected versus 19.4% of non-obese patients (p=0.000). No significant associations were observed for gender, hypertension, or symptom duration. Conclusion: Peripheral neuropathy is prevalent in newly diagnosed Type II Diabetes Mellitus patients, particularly among older and obese individuals. Early screening and targeted interventions focused on these risk factors may help reduce neuropathy-related complications.